THE ESSENTIAL OF COMPARATIVES POLITICAL INSTITUTIONS IN AFRICAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Comparative political institution are the organizations in a government that create, enforce, and apply laws. They often mediate conflict, make governmental policy on the economy and social systems, and otherwise provide representation for the population.In general, democratic political regimes are divided into two types: presidential (headed by a president) and parliamentary (headed by a parliament). Legislatures built to support the regimes are unicameral (only one house) or bicameral (two houses—for example, a senate and a house of representatives or a house of commons and a house of lords).Party systems can be two-party or multiparty and the parties can be strong or weak depending on their level of internal cohesion. The political institutions are those bodies—parties, legislatures, and heads of state—that make up the whole mechanism of modern governments.In other words Comparative Politics is concerned with behavior, institutions, processes, ideas and values present in more than one country.  It  searches  for  those  regularities  and  patterns,  those  similarities  and differences between more than one nation state that help clarify the basic nature, working and belief of regimes. Comparative Politics studies a broader range of Political activity, including governments and their institution as well as other forms of organization not directly related to national government; for  example  ,tribes,  communities,  associations,  Unions  etc.  Comparative Politics, like Political